PENGGUNAAN QR CODE BERBASIS KRIPTOGRAFI ALGORITMA AES ADVANCED ENCRYPTION STANDARD UNTUK ADMINISTRASI REKAM MEDIS: USING QR CODE BASED ON AES ADVANCED ENCRYPTION STANDARD CRYPTOGRAPHY ALGORITHM FOR MEDICAL RECORD ADMINISTRATION - Ferdiansyah Ferdian; Asep Id Hadiana Asep Id; Fajri Rakhmat Umbara Fajri Rakhmat (Journal of Information Technology, 2021)
Administrative data in health can contain some important information, such as the identity of patients, doctors, and even health facilities. Data security is needed to maintain confidentiality and prevent parties who do not misuse the data. The purpose of this study is to answer the gap that exists with the use of QR Code Documents. Then the QR Code is divided for Administrative Management. In previous studies using QR codes based on Cryptography for administrative data systems in the health sector. In this study, confidential information data messages are embedded into a Cryptographic-based QR code using the AES Advanced Encryption Standard Method. The QR code will correct the error generated by the secret embedding procedure into the document, then the QR code can validate to display the data. The author conducted testing with brute force and AES methods to ensure the security of the application running properly in the data. The result of this research is that the QR code can enter Medical Record Administration data documents using the AES method. With this, it is expected to significantly reduce the potential for data leakage from the Medical Record Administration. The conclusion of the authors in this study aims to perform data administration by using a QR Code based on Cryptography. The author has presented an approach to accessing data using the storage technology used for authentication when performing data administration requests. The use of this AES Advanced Encryption Standard security method provides the advantages of ease of use and efficient use of resources